Association of HIV Associated Neurocognitive Disorder with Mini-Mental State Examination Score – A Cross-Sectional Study - Dr. Gaurav Sharma; Dr. Gaurav Sharma; Dr. S. Chandrawanshi; Dr. D.P. Lakra; Dr. Surbhi Dubey (International Journal of Pharma and Bio Sciences, 2023)
Even in the era of ART (Antiretroviral Therapy), HIV Associated Neurocognitive Disorder (HAND) is still prevalent. It may have been associated in some way with CD4 counts, disease duration, and the duration of treatments. This cross-sectional study was conducted at a tertiary care hospital in Raipur, Chhattisgarh, India. To determine the association of HIV-associated neurocognitive disorder with mini-mental state examination score (MMSES) and its correlation with CD4 counts, disease duration, and art regimen. Patients who meet the inclusion criteria are seen at the ART Centre, in the clinical OPD outpatient department, or hospitalized in the medical ward throughout the year from November 2021 to October 2022. People living with HIV(PLWH) underwent screening-validated methods to diagnose HIV-associated neurocognitive disorders (HAND) in central India. This study includes 92 HIV patients in total. The mean age of study subjects was 37.5 ± 12.76 years. 60.87% were male, and 39.13% were female study subjects. The mean mental score and CD4 counts among the study subjects were 23.29 ± 0.30 with [CI: 22.68-23.90] and 346.04 ± 22.29 with [301.75-390.33], respectively, and the prevalence of HAND was 52.17%. Between HAND, CD4 counts, and HIV disease duration, a significant correlation was found. This study concludes that the MMSES is a test for detecting HIV-associated neurocognitive disorder and the correlation between HAND and CD4 counts and HIV disease duration. Disease. However, the correlation between HAND and the duration of the ART regimen was insignificant.